2018
DOI: 10.1007/s00114-018-1572-y
|View full text |Cite
|
Sign up to set email alerts
|

Floral colour change in Byrsonima variabilis (Malpighiaceae) as a visual cue for pollen but not oil foraging by oil-collecting bees

Abstract: Pollinators search for multiple flora resources throughout their life cycle. Most studies, however, only assess how bees discriminate floral cues in the context of nectar foraging. In the present study, we sought to elucidate whether oil-collecting bees discriminate flowers of Byrsonima variabilis (Malpighiaceae) with petals of different colours when foraging for pollen or oil. As the colour of the standard petal changes during anthesis, we characterised the spectral reflectance patterns of flowers throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…We observed that T. spinipes and A. mellifera preferred to visit orange and yellow flowers. Results for Byrsonima variabilis (Malpighiaceae) were similar to ours, in which large and small bees showed greater preference for orange and yellow flowers during the collection of floral resources (pollen and nectar) [ 24 ].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…We observed that T. spinipes and A. mellifera preferred to visit orange and yellow flowers. Results for Byrsonima variabilis (Malpighiaceae) were similar to ours, in which large and small bees showed greater preference for orange and yellow flowers during the collection of floral resources (pollen and nectar) [ 24 ].…”
Section: Resultssupporting
confidence: 75%
“…They also prove that bees visit fewer red flowers due to their higher emissions (above 700 nm) and high chlorophyll fluorescence index in this band. Furthermore, our outcomes suggest that flower fluorescence pattern is an important signal in flower recognition by visiting bees [ 15 , 16 , 24 , 61 ]; therefore, our findings raise new possibilities in the perception of floral visitors since fluorescence was not considered important in attracting bees to different T. majus flowers.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In our experiment we chose stimuli that would be relatively difficult for bees to discriminate, to both be ecologically realistic (in natural foraging scenarios bees often need to discriminate between stimuli this similar in colour e.g. 89 ), and to maximize the chances that we would detect an effect on learning if it existed in this context. We also replicated the experiment across two different scenarios where the motivational value of the US changed, as well as the opportunity to learn.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this floral UV category could be related with resource signalling, since yellow and UVabsorbing pollen and anthers (or mimics) trigger behavioural responses in bees and flies (Lunau et al, 2017 and references therein). Interestingly, oil-collecting bees are sensitive to floral visual changes (Ferreira and Torezan-Silingardi, 2013;Melo et al, 2018) and half of the Malpighiaceae species (mainly having oil as resource) show UV-absorbing reproductive structures (CR), a pattern usually associated with pollen-flowers (Lunau et al, 2017).…”
Section: Floral Uv Features and Plant-pollinator Interactionmentioning
confidence: 99%